Method for improving fast charging performance of silicon-carbon composite material
By using heteroatom-doped MOF materials in silicon carbon materials to deposit nanosilicon and coat graphene and lithium-doped amorphous carbon, the low magnification and cyclic performance problems of silicon carbon materials are solved, and the efficient fast charging and Stable cycle.
Patent Information
- Application Number
- CN202411167789.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The first-time efficiency and fast charging performance of silicon-carbon materials are low, and the expansion of nano-silicon during charging and discharging leads to a deviation in the material's cyclic performance, and it is difficult for the prior art to effectively improve its magnification and cyclic performance.
Use heteroatom-doped MOF materials as carriers to deposit nanosilicon in their pores, and coat the surface with graphene and lithium doped amorphous carbon to enhance the electron and ionic conductivity of the material, reduce the expansion of nanosilicon, and improve the magnification. and cycle performance.
It significantly improves the rate performance and cyclic performance of silicon-carbon composite materials, reduces expansion during charging and discharging, improves electronic conductivity and ionic conductivity, and enhances the fast charging and cyclic performance of the material.
Smart Images

Figure CN119284909A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium ion battery material preparation, and specifically is a method for improving the fast charging performance of silicon-carbon composite materials. Background Art
[0002] Silicon-carbon materials are composed of porous carbon and nano-silicon deposited between the pores. Due to the high specific surface area and poor electronic conductivity of porous carbon itself, the initial efficiency and fast charging performance of the material are reduced. At the same time, the expansion of nano-silicon during charging and discharging causes deviations in the material's cycle performance. Therefore, it is necessary to dope the porous carbon to improve the electronic conductivity of the material, and to coat the porous carbon to improve the electronic and ionic conductivity of the material, thereby improving the rate and cycle performance of the material. For example, Chinese patent application No. 202410056002.6 discloses a method for preparing a rare earth-doped amorphous carbon-coated silicon-carbon composite material, which first prepares lithium-doped porous carbon, then deposits metallic lithium by decomposition of lithium hydride, and passes silane gas nano-silicon to deposit, thereby obtaining a lithium-doped silicon-carbon precursor material; and coating the surface with rare earth-doped amorphous carbon to obtain a silicon-carbon composite material. Due to the uneven pore size distribution and small pore volume of the inner core, and the limited improvement of the electronic conductivity of the material by the rare earth-doped amorphous carbon in the outer layer, the fast charging performance and cycle performance of the composite material are limited. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned shortcomings and provide a method for improving the fast charging performance of silicon-carbon composite materials by improving the rate performance and cycle performance.
[0004] A method for improving the fast charging performance of a silicon-carbon composite material of the present invention comprises the following steps:
[0005] Step S1: adding the imidazole derivative, chloride salt and heteroatom compound to the DMF solution according to the mass ratio of imidazole derivative: chloride salt: heteroatom compound: DMF (N,N-dimethylformamide) = (100-200): 100: 1-5: 500-1500, and transferring to a high-pressure reactor, reacting for 1-6 hours at a temperature of 50-120° C. and a pressure of 1-2 MPa, filtering, washing with acetone for 3 times, and then soaking in methanol for 24 hours, filtering, and freeze-drying the obtained filter residue at -40° C. for 24 hours to obtain a heteroatom-doped MOF material;
[0006] Step S2: transferring the heteroatom-doped MOF material to a fluidized bed, heating it to 450-550° C., introducing silane gas at a flow rate of 50-200 SCCM for 30-300 min, then heating it to 850-1000° C., introducing heteroatom gas at a flow rate of 10-100 SCCM for 30-300 min, then cooling it to 300-450° C., evacuating it to a vacuum degree of 0.1-0.5 MPa, introducing oxygen passivation gas at a flow rate of 50-200 SCCM for 30-300 min, and then cooling it to room temperature to obtain a silicon-carbon precursor material;
[0007] Step S3: According to the mass ratio of resin: 1-5wt% graphene oxide solution: silicon-carbon precursor: dispersant = 5-15: 100: 100: 1-5, the resin is added to the organic solvent to prepare a 1-10wt% solution, and then the graphene oxide solution, silicon-carbon precursor and dispersant with a concentration of 1-5wt% are added and dispersed evenly, and spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h), and then the resulting material is transferred to a tubular furnace, heated to 700-1000°C, and hydrogen is introduced at a flow rate of 10-100SCCM for 60-600min to obtain a silicon-carbon composite material.
[0008] The imidazole derivative described in step S1 is one of 2-mercaptoimidazole, 4-formylimidazole, N-butylimidazole, 2-propylimidazole, methimazole or 2-hydroxybenzimidazole; the chloride salt is one of ferric chloride hexahydrate, aluminum chloride hexahydrate, tin tetrachloride pentahydrate or zirconium chloride hydrate; the heteroatom compound is one of melamine, urea, phosphoric acid, boric acid or ammonia.
[0009] The heteroatom gas in step S2 is one of ammonia, hydrogen sulfide or boron trichloride.
[0010] The resin described in step S3 is one of phenolic resin, epoxy resin or furfural resin; the organic solvent is one of benzene, xylene, methanol, ethanol, 1,4-butanediol or acetone; the dispersant is one of lithium carboxymethyl cellulose, lithium polyacrylate or lithium polyvinyl alcohol.
[0011] Compared with the prior art, the present invention has obvious beneficial effects. It can be seen from the above technical scheme that the present invention first prepares a heteroatom-doped MOF material, deposits nano-silicon in its pores, and coats the outer layer with graphene-doped amorphous carbon. Heteroatom-doped MOF materials, by utilizing the adjustable chemical structure, high specific surface area, large pore size and pore volume of metal organic framework materials (MOFs), can reduce the expansion of nano-silicon during the charging and discharging process of the material, thereby improving the electronic conductivity of the material and improving the rate performance. Graphene and amorphous carbon are coated on the surface of the silicon-carbon precursor to improve the electronic conductivity of the material and to restrain the expansion of nano-silicon during the charging and discharging process; at the same time, the coating liquid contains a lithium dispersant, and lithium-doped amorphous carbon is obtained after carbonization, which improves the electronic and ionic conductivity of the material and improves the rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is the SEM image of the silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION
[0013] Embodiment 1:
[0014] A method for improving the fast charging performance of a silicon-carbon composite material comprises the following steps:
[0015] Step S1: 150 g of 4-formyl imidazole, 100 g of ferric chloride hexahydrate and 3 g of melamine were added to 1000 g of DMF solution, and transferred to a high-pressure reactor, reacted at a temperature of 80° C. and a pressure of 1.5 MPa for 3 h, filtered, washed with acetone 3 times, then soaked in methanol for 24 h, filtered, and the obtained material was freeze-dried at -40° C. for 24 h to obtain a heteroatom-doped MOF material;
[0016] Step S2: The heteroatom-doped MOF material is transferred to a fluidized bed, heated to 500°C, and then silane gas (SiH4) is introduced by a silane cracking method at a flow rate of 100SCCM for 150min, then the temperature is raised to 950°C and ammonia gas is introduced at a flow rate of 50SCCM for 150min, then the temperature is lowered to 400°C, evacuated to a vacuum degree of 0.3Mpa, oxygen passivation gas is introduced at a flow rate of 100SCCM for 150min, and then the temperature is lowered to room temperature to obtain a silicon-carbon precursor material;
[0017] Step S3: Add 10g of phenolic resin to 200g of xylene organic solvent to prepare a 5wt% solution, then add 100g, 3wt% graphene oxide solution, 3g of lithium carboxymethyl cellulose, and 100g of silicon-carbon precursor to disperse evenly, spray dry (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h), then transfer the resulting material to a tubular furnace, heat to 850°C, and introduce hydrogen at a flow rate of 50SCCM for 150min to obtain a silicon-carbon composite material.
[0018] Embodiment 2:
[0019] A method for improving the fast charging performance of a silicon-carbon composite material comprises the following steps:
[0020] Step S1: 100 g of 2-propylimidazole, 100 g of aluminum chloride hexahydrate and 1 g of urea were added to 500 g of DMF solution and transferred to a high-pressure reactor, followed by reaction at a temperature of 50° C. and a pressure of 2 MPa for 6 h, filtration, washing with acetone for 3 times, and then soaking in methanol for 24 h, filtration, and freeze-drying the obtained material at -40° C. for 24 h to obtain a heteroatom-doped MOF material;
[0021] Step S2: The heteroatom-doped MOF material is transferred to a fluidized bed, heated to 450°C, and then silane (SiH4) gas is introduced by a silane cracking method at a flow rate of 50SCCM for 300min, then the temperature is raised to 850°C and hydrogen sulfide gas is introduced at a flow rate of 10SCCM for 300min, then the temperature is lowered to 300°C, evacuated to a vacuum degree of 0.1Mpa, oxygen passivation gas is introduced at a flow rate of 50SCCM for 300min, and then the temperature is lowered to room temperature to obtain a silicon-carbon precursor material;
[0022] Step S3: Add 5g of epoxy resin to 500g of methanol organic solvent to prepare a 1wt% solution, then add 100g, 1wt% graphene oxide solution, 1g of lithium polyacrylate, and 100g of silicon-carbon precursor to disperse evenly, spray dry (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h), then transfer the resulting material to a tubular furnace, heat to 700°C, and introduce hydrogen at a flow rate of 10SCCM for 600min to obtain a silicon-carbon composite material.
[0023] Embodiment 3:
[0024] A method for improving the fast charging performance of a silicon-carbon composite material comprises the following steps:
[0025] Step S1: 200 g of methimazole, 100 g of tin tetrachloride pentahydrate and 5 g of phosphoric acid are added to 1500 g of DMF solution, and transferred to a high-pressure reactor, and then reacted at a temperature of 120° C. and a pressure of 1 MPa for 1 h, filtered, washed with acetone 3 times, and then soaked in methanol for 24 h, and freeze-dried at -40° C. for 24 h to obtain a heteroatom-doped MOF material;
[0026] Step S2: The heteroatom-doped MOF material is transferred to a fluidized bed, heated to 550°C, and then silane (SiH4) gas is introduced by a silane cracking method at a flow rate of 200SCCM for 30 minutes, then the temperature is raised to 1000°C and boron trichloride gas is introduced at a flow rate of 100SCCM for 30 minutes, then the temperature is lowered to 450°C, and the vacuum is evacuated to a vacuum degree of 0.5Mpa, oxygen passivation gas is introduced at a flow rate of 200SCCM for 30 minutes, and then the temperature is lowered to room temperature to obtain a silicon-carbon precursor material;
[0027] Step S3: Add 15g of furfural resin to 150g of ethanol organic solvent to prepare a 10wt% solution, then add 100g, 5wt% graphene oxide solution, 5g of lithium polyvinyl alcohol, and 100g of silicon-carbon precursor to disperse evenly, spray dry (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h), then transfer the obtained material to a tubular furnace, heat to 1000°C, and introduce hydrogen at a flow rate of 100SCCM for 60min to obtain a silicon-carbon composite material.
[0028] Comparative Example 1:
[0029] A method for preparing a silicon-carbon composite material, comprising:
[0030] The difference from Example 1 is that the heteroatom-doped MOF material in step S1 is replaced by porous carbon (Japan Kuraray Co., Ltd., YP-50F), and the rest is the same as Example 1.
[0031] Comparative Example 2:
[0032] A method for preparing a silicon-carbon composite material, comprising:
[0033] The difference from Example 1 is that graphene oxide solution and lithium carboxymethyl cellulose are not added in step S3, and the rest is the same as Example 1.
[0034] Test Example 1:
[0035] The silicon-carbon composite material prepared in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the composite material prepared in Example 1 is a porous structure with a particle size between 5-10 μm.
[0036] Test Example 2: Physical and Chemical Performance Test
[0037] The tap density and specific surface area of the silicon composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested according to the method of the national standard GBT-38823-2020 "Silicon Carbon". The powder resistivity of the material was tested by a four-probe tester. The test results are shown in Table 1.
[0038] Table 1
[0039]
[0040] Test Example 3: Button Battery Test
[0041] The silicon composite materials in Examples 1-3 and Comparative Examples 1-2 are used as negative electrode materials for lithium-ion batteries and assembled into button batteries. The specific method for the negative electrode material is as follows: adding a binder, a conductive agent and a solvent to the composite material, stirring and slurrying, coating on a copper foil, drying and rolling to obtain the result. The binder used is LA132 binder, the conductive agent is SP, and the solvent is double distilled water. According to the composite material: SP: LA132: double distilled water = 90g: 4g: 6g: 250mL, a negative electrode plate is prepared; a metal lithium sheet is used as the positive electrode; the electrolyte uses LiPF6 / EC+DEC, in which LiPF6 is the electrolyte, a mixture of EC and DEC with a volume ratio of 1:1 is the solvent, and the electrolyte concentration is 1.3mol / L; the diaphragm uses a composite film of polyethylene PE, polypropylene PP or polyethylene propylene PEP. The button battery is assembled in an argon-filled glove box. The electrochemical properties were tested on a Wuhan Blue Electric CT2001A battery tester with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. The first discharge capacity and first efficiency of the button cell were tested. The charging DCR (50% SOC) and cycle performance (0.2C / 0.2C, 100 times) were also tested. When the button cell was fully charged at 100% SOC, the expansion rate of the negative electrode was tested. At the same time, the liquid absorption capacity of the negative electrode was tested (1 mL of electrolyte was dripped onto the negative electrode until the electrolyte was completely absorbed and the time t was recorded). The test results are shown in Table 2.
[0042] Table 2
[0043]
[0044] It can be seen from Table 1 and Table 2 that the embodiment is superior to the comparative example in specific capacity, DCR, expansion and cycle performance. The reason is that the MOF material has low full-charge expansion and high specific surface area, which improves the cycle performance; at the same time, the electronic and ionic conductivity of the material is improved by doping with graphene and lithium salt, thereby improving the initial efficiency and reducing the DCR.
[0045] Test Example 4: Soft-pack battery test
[0046] The silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-2 were mixed with 90% artificial graphite as negative electrodes, and slurry mixing and coating were performed to prepare negative electrode sheets. 1 / 3 Co 1 / 3 Mn 1 / 3 A 2Ah soft-pack battery was prepared using Li O2) as the positive electrode, Li PF6 (solvent is EC+DEC, volume ratio is 1:1, electrolyte concentration is 1.3 mol / L) as the electrolyte, and Celgard2400 membrane as the separator.
[0047] 4.1HPPC rate performance test:
[0048] The rate performance of the soft pack battery was tested with a charge and discharge voltage range of 2.5 to 4.2 V and a temperature of 25 ± 3.0 °C. The resistance of the battery under different SOC conditions (90%, 70%, 50%, 30%, 10%, 5%) was tested at 3C and the battery was discharged at 4.0C. The test results are shown in Table 3.
[0049] Table 3
[0050]
[0051] It can be seen from Table 3 that the impedance of the soft-pack battery of the silicon composite material prepared by the materials of Examples 1-3 is significantly lower than that of Comparative Examples 1-2, that is, the charging time is shorter. The reason for this is that lithium ions need to migrate during the battery charging process, the example materials have low powder resistivity and their porous metal framework MOF materials have strong liquid absorption capacity and high lithium ion conductivity, which reduces impedance and DCR.
[0052] 4.2 Cycle performance test:
[0053] The obtained soft pack battery was subjected to a cycle performance test under the following conditions: charge and discharge current 1C / 1C, voltage range 2.5-4.2V, cycle number 500 times, and its 500 times charging DCR (50% SOC) was tested. The test results are shown in Table 4.
[0054] Table 4
[0055] project Retention rate after 500 cycles (%) Charging DCR(mΩ) Example 1 94.76 19.34 Example 2 93.03 21.05 Example 3 95.51 18.53 Comparative Example 1 88.36 24.63 Comparative Example 2 90.91 28.12
[0056] It can be seen from Table 4 that the cycle performance of the lithium ion battery prepared using the composite materials obtained in Examples 1-3 is significantly better than that of Comparative Examples 1-2. The experimental results show that the reason is that the example materials have low expansion and low powder resistivity, which reduces the lithium ions consumed by repeated repair of SE I during charging and discharging, thereby improving the cycle performance.
[0057] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for improving the fast charging performance of a silicon-carbon composite material, comprising the following steps: Step S1: adding the imidazole derivative, chloride salt and heteroatom compound to the DMF solution according to the mass ratio of imidazole derivative: chloride salt: heteroatom compound: DMF = (100-200): 100: 1-5: 500-1500, and transferring to a high-pressure reactor, reacting at a temperature of 50-120° C. and a pressure of 1-2 MPa for 1-6 hours, filtering, washing with acetone for 3 times, and then soaking in methanol for 24 hours, filtering, and freeze-drying the obtained filter residue at -40° C. for 24 hours to obtain a heteroatom-doped MOF material; Step S2: transferring the heteroatom-doped MOF material to a fluidized bed, heating it to 450-550° C., introducing silane gas at a flow rate of 50-200 SCCM for 30-300 min, then heating it to 850-1000° C., introducing heteroatom gas at a flow rate of 10-100 SCCM for 30-300 min, then cooling it to 300-450° C., evacuating it to a vacuum degree of 0.1-0.5 MPa, introducing oxygen passivation gas at a flow rate of 50-200 SCCM for 30-300 min, and then cooling it to room temperature to obtain a silicon-carbon precursor material; Step S3: According to the mass ratio of resin: 1-5wt% graphene oxide solution: silicon-carbon precursor: dispersant = 5-15:100:100:1-5, the resin is added to the organic solvent to prepare a 1-10wt% solution, and then the graphene oxide solution with a concentration of 1-5wt%, the silicon-carbon precursor, and the dispersant are added to disperse evenly, and spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h), and then the obtained material is transferred to a tubular furnace, heated to 700-1000°C, and hydrogen is introduced at a flow rate of 10-100SCCM for 60-600min to obtain a silicon-carbon composite material.
2. A method for improving the fast charging performance of a silicon-carbon composite material as described in claim 1, wherein the imidazole derivative described in step S1 is one of 2-mercaptoimidazole, 4-formyl imidazole, N-butyl imidazole, 2-propyl imidazole or methimazole or 2-hydroxybenzimidazole; the chloride salt is one of ferric chloride hexahydrate, aluminum chloride hexahydrate, tin tetrachloride pentahydrate or zirconium chloride hydrate; the heteroatom compound is one of melamine, urea, phosphoric acid, boric acid or ammonia water.
3. A method for improving the fast charging performance of a silicon-carbon composite material as described in claim 1, wherein the heteroatom gas described in step S2 is one of ammonia, hydrogen sulfide or boron trichloride.
4. A method for improving the fast charging performance of a silicon-carbon composite material as described in claim 1, wherein the resin described in step S3 is one of a phenolic resin, an epoxy resin or a furfural resin; the organic solvent is one of benzene, xylene, methanol, ethanol, 1,4-butanediol or acetone; and the dispersant is one of lithium carboxymethyl cellulose, lithium polyacrylate or lithium polyvinyl alcohol.
Citation Information
Patent Citations
Preparation method of rare earth doped amorphous carbon coated silicon-carbon composite material
CN117832456A
Preparation method of platinum quantum dot doped graphene-based conductive ink, conductive ink and application thereof
CN111410872A
Method for preparing high-conductivity fluororubber sealing material through ionic liquid assisted dispersion
CN115584095A
Silicon-carbon composite negative electrode material, preparation method thereof and lithium ion battery
CN116053431A
Silicon-carbon composite material, preparation method thereof, negative electrode material and lithium ion battery
CN117352685A
Cited By
Preparation method of double-coated silicon-carbon composite material, electrode and lithium battery
CN121687937A
Method for preparing double-coated silicon-carbon composite material, electrode and lithium battery
CN121687937B
Preparation method and application of fast ion conductor coated silicon-carbon composite material
CN121812564A